Evaluation of COVID-19 vaccine breakthrough infections among immunocompromised patients fully vaccinated with BNT162b2. (1st January 2021) - Di Fusco, Manuela; Moran, Mary M.; Cane, Alejandro; Curcio, Daniel; Khan, Farid; Malhotra, Deepa; Surinach, Andy; Miles, Amanda; Swerdlow, David; McLaughlin, John M.; Nguyen, Jennifer L.
Abstract: Objective: To evaluate COVID-19 vaccine breakthrough infections among immunocompromised (IC) individuals. Methods: Individuals vaccinated with BNT162b2 were selected from the US HealthVerity database (10 December 2020 to 8 July 2021). COVID-19 vaccine breakthrough infections were examined in fully vaccinated (≥14 days after 2nd dose) IC individuals (IC cohort), 12 mutually exclusive IC condition groups, and a non-IC cohort. IC conditions were identified using an algorithm based on diagnosis codes and immunosuppressive (IS) medication usage. Results: Of 1, 277, 747 individuals ≥16 years of age who received 2 BNT162b2 doses, 225, 796 (17.7%) were identified as IC (median age: 58 years; 56.3% female). The most prevalent IC conditions were solid malignancy (32.0%), kidney disease (19.5%), and rheumatologic/inflammatory conditions (16.7%). Among the fully vaccinated IC and non-IC cohorts, a total of 978 breakthrough infections were observed during the study period; 124 (12.7%) resulted in hospitalization and 2 (0.2%) were inpatient deaths. IC individuals accounted for 38.2% ( N  = 374) of all breakthrough infections, 59.7% ( N  = 74) of all hospitalizations, and 100% ( N  = 2) of inpatient deaths. The proportion with breakthrough infections was 3 times higher in the IC cohort compared to the non-IC cohort ( N  = 374 [0.18%] vs. N  = 604 [0.06%]; unadjusted incidence rates were 0.89 and 0.34 per 100 person-years, respectively. Organ transplant recipients had the highest incidence rate; those with >1 IC condition, antimetabolite usage, primary immunodeficiencies, and hematologic malignancies also had higher incidence rates compared to the overall IC cohort. Incidence rates in older (≥65 years old) IC individuals were generally higher versus younger IC individuals (<65). Limitations: This retrospective analysis relied on coding accuracy and had limited capture of COVID-19 vaccine receipt. Conclusions: COVID-19 vaccine breakthrough infections are rare but are more common and severe in IC individuals. The findings from this large study support the FDA authorization and CDC recommendations to offer a 3rd vaccine dose to increase protection among IC individuals.